Face to Face: A Conversation with Vittorio Rossi - Reid, Gregory J. (Theatre Research in Canada / Recherches théâtrales au Canada, 2000)
With productions of nine of his plays behind him (including his translation of Eduardo de Filippo’s Filumena for the Stratford Festival in 1997), playwright and actor Vittorio Rossi has become one of Canada’s best-known dramatists of Italian origin. He began his writing career by winning the Best New Play Award at the Quebec Drama Festival twice: for "Little Blood Brother" in 1986 and for "Backstreets" in 1987. His first full-length play, The Chain, broke attendance records at Centaur Theatre, English Quebec’s main stage. His most acclaimed drama, The Last Adam, won the Canadian Authors Association Literary Award for Drama in 1996. Rossi’s career as an actor, in addition to his work in his own plays, has included roles in such films as Snake Eater II: The Drug Buster (1991), Canvas: The Fine Art of Crime (1992), Le Sphinx (1995), Strip Search (1997), Suspicious Minds (1997), and the award-winning Post Mortem (1999); and televison series such as Malarek (1989), Urban Angel (1991), Bonanno: A Godfather’s Story (1999) and the number-one-rated television show in Quebec for its three-year run, Omerta (1996, 1997, 1998). I met with Rossi at the Café Via Crescent on Crescent Street in Montreal, December 8, 1999. We discussed the situation of actors in Canada, the process of translation and adaptation, the background of the plays and his reaction to their critical reception, and his work in progress: the film adaptation of a crime novel for Denys Arcand, the scripting of a television series with Luc Dionne (creator of Omerta) and the film adaptation and production of Rossi’s own shoe-store drama Scarpone. Le dramaturge et comédien Vittorio Rossi, dont neuf pièces ont été mises en scène (incluant sa traduction de Filumena d’Eduardo de Filippo au Festival de Stratford en 1997), est aujourd’hui l’un des plus importants dramaturges canadiens d’origine italienne. Dès ses débuts comme écrivain pour le théâtre, il remportait à deux reprises le Prix de la meilleure nouvelle pièce au Festival de théâtre de Québec: en 1986 pour «Little Blood Brother» et en 1987 pour «Backstreets». Sa première pièce en deux actes, The Chain, a attiré des foules record au Théâtre Centaur, principal théâtre de langue anglaise au Québec. Il a obtenu en 1996 le Prix littéraire pour le théâtre de l’Association des auteurs canadiens, pour son plus grand succès, The Last Adam. En plus de participations comme acteur dans ses propres pièces, Rossi a aussi joué au cinéma, notamment dans Snake Eater II: The Drug Buster (1991), Canvas: The Fine Art of Crime (1992), Le Sphinx (1995), Strip Search (1997), Suspicious Minds (1997) et dans le film primé Post Mortem (1999). On a aussi pu le voir dans les séries télévisées Malarek (1989), Urban Angel (1991), Bonanno: A Godfather’s Story (1999), de même que dans la très populaire série Omertà, qui a été présentée pendant trois ans à la télévision québécoise (1996, 1997, 1998). J’ai rencontré Vittorio Rossi au Café Via Crescent, rue Crescent, à Montréal, le 8 décembre 1999. Nous avons discuté de la situation des acteurs au Canada, de la traduction et de l’adaptation, de la genèse de ses pièces et de ses réactions devant leur réception critique, et enfin de ses travaux en cours: l’adaptation cinématographique d’un roman policier pour Denys Arcand, le scénario d’une nouvelle série pour la télé avec Luc Dionne (créateur d’Omertà) et l’adaptation et la production cinématographiques d’une de ses propres œuvres dramatiques, Scarpone.